Study of the morphological characteristics of nanoparticles synthesized by biogenic method (LACCEI, 2024)
The green nanotechnology (biogenic method) is recognized for its broad advantages in different branches of the scientific field. In recent years, has been defined as an innovated field, related to the development of methodologies with little environmental contamination. In this research, the PRISMA methodology was applied, considered some selection criteria (Open access, language, quartile), obtaining a total of 31 investigation. This research concludes the direct influence of the extract and the size of the nanoparticles, and in that this factor is highly variable due to the dependence of its properties on their phytoconstituents and the territory. furthermore, a trend in the formation of spherically shape nanomaterials was identified. and finally, it is recognized that through the biogenic synthesis the formation of nanostructures was crystalline, obtaining a considerable level of purity in each nanoparticle considered.